Pengaruh Metode 5’S (Swadding, Stomach Position, Sushing, Swingging, Sucking) terhadap Respon Nyeri Bayi Setelah Imunisasi HB-0 - Syatriawati Syatriawati; Iskandar Markus Sembiring (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Immunization is a source of acute pain in infants that can cause trauma, nonpharmacological techniques that can be done is by giving of 5'S method(swaddling, stomach position, sushing, swinging, and sucking) which are effective and easy to do and the purpose of this study was to find out whether there is an effect of 5'Smethod (swaddling, stomach position, sushing, swinging and sucking) on pain response in infants after Hb-0 immunization at Grandmed Hospital LubukPakam, the method and design of this study was Quasy Experiment with one group pre test and post test design. the population in this study were infants aged0-7 days who received Hb-0 immunization, amounting to 40 people with purposive sampling technique according to inclusion criteria and pain measurement uses the NIPS (Neonatal Infant Pain Scale) pain scale, the data analysis was performed by Paired Sample t-test with a confidence level of 0.05%, the results of the study were lower pain in the treatment group with p = 0.0000 <0.05 (<ɑ), the conclusion of this study is that there was an effect of the 5'S method (swaddling, stomach position, sushing, swinging, and sucking) on pain response in infants after Hb-0 immunization.Immunization is a source of acute pain in infants that can cause trauma, nonpharmacological techniques that can be done is by giving of 5'S method(swaddling, stomach position, sushing, swinging, and sucking) which are effective and easy to do and the purpose of this study was to find out whether there is an effect of 5'Smethod (swaddling, stomach position, sushing, swinging and sucking) on pain response in infants